2009
DOI: 10.1073/pnas.0912134107
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ST-246 versus lethal poxvirus challenge in immunodeficient mice

Abstract: The threat of smallpox as a bioweapon and the emerging threat of human monkeypox, among other poxviral diseases, highlight the need for effective poxvirus countermeasures. ST-246, which targets the F13L protein in vaccinia virus and its homologs in other orthopoxvirus species, provides full protection from lethal poxviral disease in numerous animal models and seems to be safe in humans. All previous evaluations of ST-246 efficacy have been in immunocompetent animals. However, the risk of severe poxviral diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 37 publications
1
43
0
1
Order By: Relevance
“…The data showed that a three-dose or nine-dose regimen of BCV extended survival of nude mice. These data are in agreement with previous reports on another VACV inhibitor, ST-246, including our own studies, demonstrating that the virostatic drug protected immune-deficient mice from lethality while they were on treatment (29,37). As expected, nude mice succumbed after BCV was stopped.…”
Section: Discussionsupporting
confidence: 82%
“…The data showed that a three-dose or nine-dose regimen of BCV extended survival of nude mice. These data are in agreement with previous reports on another VACV inhibitor, ST-246, including our own studies, demonstrating that the virostatic drug protected immune-deficient mice from lethality while they were on treatment (29,37). As expected, nude mice succumbed after BCV was stopped.…”
Section: Discussionsupporting
confidence: 82%
“…The therapeutic window of ST-246 provides a feasible approach to protect such individuals from vaccine related adverse reactions, including generalized vaccinia. Previous studies have shown that ST-246 significantly extended the survival of nude and SCID mice after lethal challenge with vaccinia virus strain WR and that mice eventually succumbed after therapy was stopped (13). In the present study, we used nude mice that were reconstituted with T cells purified from naive BALB/c mice in order to better mimic different patient groups with various levels of T cell immune deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, the daily administration of ST-246 for 5 to 14 days has been shown to protect normal mice from lethal intranasal challenge with ectromelia and cowpox viruses (11,12). In immune-deficient mice, protection was observed in mice receiving treatment; however, the mice succumbed after ST-246 treatment ceased (13). Importantly, in nonhuman primates, ST-246 has been shown to protect from poxvirus disease, reduce viral loads, and enhance survival (14).…”
mentioning
confidence: 99%
“…Postponing treatment until 72 h after disease diminished ST-246 adequacy in a few models however gave full insurance from deadly test in most. These discoveries propose that ST-246 may be successful in controlling smallpox or other pathogenic orthopoxviruses in some immunodeficient human populaces for whom the antibody is contraindicated (Grosenbach et al, 2010).…”
Section: Treatment Of Immune-deficient Host With St-246mentioning
confidence: 99%